Hacker's delight - Warren, Henry S. (Upper Saddle River, NJ Addison-Wesley, 2013)
Compiles programming hacks intended to help computer programmers build more efficient software, in an updated edition that covers cyclic redundancy checking and new algorithms and that includes exercises with answers.
Includes bibliographical references (pages 471-479) and index.
Keywords: Computer programming